RETHINKING SOCIABLE GREEN SPACES AMID THE COVID-19 CRISIS: A CASE STUDY OF BATAM, INDONESIA - Carissa Dinar Aguspriyanti (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: One of the lasting impacts of the COVID-19 crisis undisputedly is changes in the way people use public spaces including green spaces. Some people despite the social isolation rules still often visit public green spaces to maintain their well-being. This study aimed to rethink how green spaces as a sociable place can be more adaptable to fulfill the new needs of people which have arisen due to the pandemic. Direct-structured observation and semi-structured interviews with purposive sampling were conducted in the park located in Batam, Indonesia. It was revealed that the use of this park as a sociable place has prioritized most on ‘relaxation’ behaviours at one time, followed by ‘affiliation’ and ‘interaction’ behaviours after the pandemic strikes. The ‘affiliation’ activities, nevertheless, were interestingly the top reason for people visiting this park more frequently in a week. The proposed post-pandemic concept of the park as a sociable green space was subsequently conceived around the circulation, furniture, and activity settings with several design strategies as a response to the key issues concerning the social behaviours and health protocol system in this park. Abstrak: Salah satu dampak jangka panjang dari krisis COVID-19 yang tidak terbantahkan adalah perubahan cara orang menggunakan ruang publik termasuk ruang terbuka hijau. Walaupun terdapat aturan isolasi sosial, beberapa orang masih sering mengunjungi ruang terbuka hijau untuk menjaga kesehatan mereka. Penelitian ini bertujuan untuk memikirkan ulang bagaimana ruang terbuka hijau sebagai ruang publik ramah atau tempat bersosialisasi dapat menjadi lebih adaptif untuk memenuhi kebutuhan baru masyarakat yang muncul akibat pandemi. Observasi langsung terstruktur dan wawancara semi terstruktur dengan purposive sampling dilakukan di taman yang terletak di Batam, Indonesia. Studi ini menemukan bahwa penggunaan taman tersebut sebagai ruang publik ramah telah memprioritaskan perilaku 'relaksasi' dalam satu waktu, diikuti oleh perilaku 'afiliasi' dan 'interaksi' setelah pandemi melanda. Namun menariknya, aktivitas yang berkaitan dengan ‘afiliasi’ menjadi alasan utama orang untuk lebih sering mengunjungi taman ini dalam satu minggu. Usulan konsep taman pasca pandemi sebagai ruang terbuka hijau ramah kemudian digagas terkait pengaturan sirkulasi, furnitur, dan aktivitas dengan beberapa strategi desain sebagai respon terhadap isu-isu utama mengenai perilaku sosial dan sistem protokol kesehatan di taman ini.